Marine Algae at Hin-Grood Reef and Koh Talu Islands, Prachuab Khiri Khan Province - แก้วสุรลิขิต, ชัชรี; ด้วงดี, ธีระพงศ์ (KKU Science Journal, 2012)
The species diversity of marine algae at Hingrood Reef and Koh Talu Islands was observed by SCUBA diving down 15 meters in July 2007. Twenty five species of 22 genera and 17 families were reported, of which, 7 species were green, 6 species were brown and 12 species were red. The dominant species were Lobophora variegata, Turbinaria conoides, T. decurrens, Hypnea spinella, Gelidiopsis variabilis, Peyssonnelia boergesenii, Pterocladiella caloglossoides and nongeniculated coralline red algae. The highest diversity, 13 species, was found in Koh Talu while 8 species were found in Hin-Grood Reef.